Evaluating Hybrid Intelligence–Supported Project-Based Learning: Effects on Students’ Learning Outcomes in Secondary Education - Miksan Ansori (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study evaluates the effect of Hybrid Intelligence-Supported Project-Based Learning (HI-PBL) on students' learning outcomes compared to standart PBL in secondary education. A quasi-experimental pretest-posttest control group design was employed with 128 students. The experimental group (n=64) received Hybrid Intelligence-Supported Project-Based Learning (HI-PBL), where students and teachers collaboratively engaged with generative AI tools to co-regulate learning processes within a structured PBL framework, while the control group (n=64) received standart PBL. Learning outcomes were measured using a 30-item cognitive achievement test (Cronbach's α = 0.881). Data were analyzed using ANCOVA with pretest scores as the covariate. After controlling for prior knowledge, students in the HI-PBL group significantly outperformed those in the conventional PBL group (F(1,125) = 25.133, p < 0.001, partial η² = 0.167), indicating a large effect size where the intervention explained 16.7% of the variance in learning outcomes. This study provides empirical evidence that integrating Hybrid Intelligence within PBL significantly enhances students' cognitive achievement. By demonstrating measurable learning gains through a covariance-controlled design, the research addresses critical gaps in AI-enhanced PBL literature, which has predominantly focused on engagement rather than achievement-based outcomes. The HI-PBL model offers a scalable approach for AI-augmented instruction that preserves teacher facilitation while leveraging AI's analytical capabilities.